KUALITAS SUMBER DAYA APARATUR DAN SISTEM INFORMASI DALAM MENINGKATKAN KINERJA PELAYANAN PUBLIK: TINJAUAN LITERATUR INTEGRATIF - Prima Yuana Sofwan Prima Yuana Sofwan; Muhamad Iqbal Inayatullah Muhamad Iqbal Inayatullah; Zaenal Abidin Zaenal Abidin; Solihin Mochtar Solihin Mochtar; Jerman Prawiranegara Jerman Prawiranegara; Cepi Hanapia Cepi Hanapia; Punjul Saeful Hayat Punjul Saeful Hayat; Andri Sumarna Andri Sumarna; Sity Syadzalia Amalia (CV. Bunda Ratu, 2026)
Public service performance increasingly depends on the alignment between civil-service capability and the information systems through which government work is coordinated. This article integrates research on apparatus quality, information-system quality, and public service performance, which are often examined separately. An integrative literature review was conducted using peer-reviewed journal articles published primarily between 2015 and 2025, complemented by four foundational studies identified through citation chaining. Thirty-one substantive articles were assessed through relevance screening, methodological appraisal, DOI verification, data extraction, and thematic synthesis. The review finds that apparatus quality is multidimensional, encompassing technical, managerial, sociocultural, and digital competencies, while information-system quality includes reliability, usability, integration, security, information accuracy, timeliness, and responsive support. Neither resource generates consistent service improvement independently. Their contribution is realized through four connected mechanisms: translating rules and data into action, augmenting employee capacity, disciplining and integrating workflows, and enabling organizational learning. Service outcomes include efficiency, accuracy, responsiveness, transparency, accessibility, consistency, and public trust. However, these outcomes are contingent on leadership, process redesign, data governance, interoperability, infrastructure, user involvement, and performance measurement. The study proposes a socio-technical complementarity model in which apparatus capability and information-system quality jointly strengthen process capability and public value. For local governments, the findings imply that competency development and system improvement should be planned, funded, and evaluated as one transformation portfolio rather than as separate administrative and technological projects. Keywords: civil-service quality, information systems, public service performance, digital government, integrative literature review